IOT Based Stepper Motor Control Using Arduino - S.Divyapriya, Suresh Kumar, Jacquline Sagaya Pushpam (International Journal of Advanced Science and Technology, 2020)
Currently, electric engines are generally utilized in numerous fields of designing and all aspects of our day by day life. Explicit sorts of electric engines are intended to meet specific applications. Right now, the size of the stepper engine control utilizing the Arduino processor through the Internet is introduced. The principle target of this paper is to plan and control the stepper engine from remote spots utilizing a Smart cell phone android application that has been created for the web of Things (IoT) and it can control the progression size of the stepper engine from remotely. The proposed stepper engine control utilizing IoTs is approved through continuous execution utilizing the Ardunio board and the website page is kept up with the assistance of web content administration. "Android" the world’s most famous versatile stage which is an instrument for making an application that looks extraordinary and exploits equipment capacities. The upside of android is that it is an open-source working framework is utilized as far as a portable application that is an advanced mobile phone which will go about as a remote control.